Analysis of E-Commerce Development in Kazakhstan: Market Structure and Key Participants - Amankulova Mukhlisa Narsafar qizi (Scientific Trends, 2025)
Kazakhstan's e-commerce is a significant part of the country's economy, and it can be identified through its market structure and key participants — retail platforms, exchange integrators, and delivery operators. This article analyzes the elements of payment systems (bank cards, mobile wallets, online aggregators) and infrastructure (warehouse networks, logistics chains, real-time tracking services). In the process of further development of e-commerce, issues that require solutions to ensure consistency of regulations, ensure cybersecurity, improve the efficiency of local delivery services and strengthen brand credibility will be identified. The article also examines Kazakhstan's integration with global e-commerce platforms (Alibaba, Amazon), regional deals for cross-border transactions, and access mechanisms to neighboring markets such as Uzbekistan and Russia. Consequently, practical recommendations will be developed on modernization of e-commerce sphere of the country.
Keywords: Economy, e-commerce, transactions, payment systems, digital infrastructure, payment systems, logistics services, retail platforms, exchange integrators, cybersecurity, global integration, brand trustworthiness.